Effect of light pulse width on frequency characteristics of photoacoustic signal – an experimental study using a pulse-width tunable LED-based photoacoustic imaging system - Agano, Toshitaka; Kuniyil Ajith Singh, Mithun; Nagaoka, Ryo; Awazu, Kunio (International Journal of Engineering and Technology, 2018)
Photoacoustic imaging is a hybrid technique that bridges the depth limits of ballistic optical imaging and the resolution limits of diffuse optical imaging. Using the acoustic waves generated in response to the absorption of pulsed light, it provides noninvasive high-resolution images of optical absorption at depths of several centimeters. This promising technique with optical contrast and ultrasonic resolution has shown potential in wide range of clinical and preclinical applications. In this work, we experimentally study the influence of light pulse width on frequency characteristics of photoacoustic signal, using an LED-based photoacoustic imaging system. We acquired photoacoustic image of the flat surface of a pencil lead at different excitation light pulse widths and the resulting frequency response of the photoacoustic temporal signal is compared with the product of Fourier transform of the light pulse and the frequency response of the ultrasound detector. Our results give a confirmation that frequency characteristics of photoacoustic signal is directly dependent on the combined response of light pulse frequencies and the frequency bandwidth of the ultrasound probe. Also, our results show that it is critical to tune pulse width of excitation light based on ultrasound probe’s frequency response, for efficient data acquisition in multiscale photoacoustic imaging.